Thermal reaction of nickel and Si0.75Ge0.25 alloy - Pey, Kin Leong (2012)
The interfacial reactions and chemical phase formation between nickel and ultrahigh vacuum chemical vapor deposited Si0.75Ge0.25 alloy have been studied within the temperature range of 300–900 °C for forming low resistive and uniform silicide films for future application in SiGe based metal–oxide–semiconductor field effect transistor devices. The silicided films were characterized by the x-ray diffraction, Auger electron spectroscopy, scanning electron microscopy, transmission electron microscopy, and micro-Raman microscopy techniques. Smooth and uniform nickel monogermanosilicide NiSi0.75Ge0.25 films have been observed for samples annealed at around 400–500 °C. For annealing temperatures of 500 °C and above, Ge-rich Si1−zGez grains where z>0.25 were found among Ge deficient Niy(SiwGe1−w)1−y grains where w<0.25 and the Niy(Si1−wGew)1−y phase is thermally stable up to an annealing temperature of 800 °C. We found that the Ni/SiGe reaction is mainly diffusion controlled with Ge and Ni as the dominant diffusing species compared to Si during the annealing process. In addition, Ge has been found to promote agglomeration especially above 700 °C, leading to an abrupt increase in the sheet resistance.